2011
DOI: 10.1089/jmf.2010.0352
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profiles of Four Wild Mushrooms and Their Potential Benefits for Hypertension Treatment

Abstract: Mushrooms are useful in balancing human diet and treating different health problems. The main determinant of the fluidity of erythrocyte membranes and rheologic properties of blood is the lipid composition of the membrane, which directly depends on lipids present in the diet. Lipid profiles of 4 European wild edible mushrooms, as well as the ability of mushroom lipids to modify the fluidity of erythrocyte membrane, were examined by using gas chromatography-mass spectometry, gas chromatography-flame ionization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
0
13
1
1
Order By: Relevance
“…Lipids of Macrolepiota procera and Collybia platyphylla provoked an increase in erythrocyte membrane fluidity, a property beneficial for hypertension treatment …”
Section: Chemical Composition and Nutritional Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Lipids of Macrolepiota procera and Collybia platyphylla provoked an increase in erythrocyte membrane fluidity, a property beneficial for hypertension treatment …”
Section: Chemical Composition and Nutritional Valuementioning
confidence: 99%
“…28 Lipids of Macrolepiota procera and Collybia platyphylla provoked an increase in erythrocyte membrane fluidity, a property beneficial for hypertension treatment. 29 The nutritional contribution of mushroom lipids is limited due to low total lipid content and a low proportion of desirable n-3 fatty acids. Nevertheless, linoleic acid is a precursor of the attractive smell of dried mushrooms.…”
Section: Lipidsmentioning
confidence: 99%
“…Apart from immune-boosting Wasser, 2002) and antitumor applications (Torisu et al, 1990;Tsang et al, 2008;Wasser, 2002), extracts of different mushrooms have also been found useful as antimicrobial (Alves et al, 2012) and antiviral (Adotey et al, 2011;Rincão et al, 2012) agents. They have also been found useful as lowering agents for serum lipids (Yoon et al, 2011a,b), blood sugar (Preuss et al, 2012;Ravi et al, 2013), and blood pressure (Abdullah et al, 2012;Mujić et al, 2011;Preuss et al, 2012), as well as many other therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the search for natural sources of functional nutrients as a food supplement has become common. Thus, it is quite important to investigate mushrooms, as a natural source of nutrients which have demonstrated potent antioxidant, anti-inflammatory, antitumoral, immunomodulatory, cardioprotective, hepatoprotective, and neuroprotective properties [1][2][3][4][5]. Since ancient times, mushrooms have been used for nutritional and medical purposes and are prevalent in several regions of the world [6][7][8].…”
Section: Introductionmentioning
confidence: 99%